Arka Przymierza w Kronice, to jest historyi świata Marcina Bielskiego - Kozaryn, Dorota (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
This article discusses the ways in which the biblical Ark of the Covenant is presented in Marcin Bielski’s Kronika, to jest historyja świata (Chronicle, that is the history of the world). The analyses point to Bielski’s use of a loanword in the form of arka or archa, the word’s translations into skrzynia (chest), and a sequence of both these terms. Bielski’s ignoring of the biblical translations of this term is also emphasised by his choice of determiners for the Ark. A search for the sources that Bielski drew from for the names he used for the Ark of the Covenant in the Vulgate, P. Comestor’s Historia scholastica, the Hebrew Bible, and the known medieval and 16th-century translations of the Bible, allows for concluding that the author felt free and unrestricted in his choices and followed guidelines known to him alone.